Genome‐wide single nucleotide polymorphism‐based autozygosity mapping facilitates identification of mutations in consanguineous families with epidermolysis bullosa. Issue 10 (19th February 2018) - Vahidnezhad, Hassan; Youssefian, Leila; Saeidian, Amir Hossein; Zeinali, Sirous; Touati, Andrew; Abiri, Maryam; Sotoudeh, Soheila; Norouz‐zadeh, Sara; Amirinezhad, Niloufar; Mozafari, Nikoo; Daneshpazhooh, Maryam; Mahmoudi, Hamidreza; et al.
Abstract: Autozygosity mapping (AM) is a technique utilised for mapping homozygous autosomal recessive (AR) traits and facilitation of genetic diagnosis. We investigated the utility of AM for the molecular diagnosis of heterogeneous AR disorders, using epidermolysis bullosa (EB) as a paradigm. We applied this technique to a cohort of 46 distinct EB families using both short tandem repeat (STR) and genome‐wide single nucleotide polymorphism (SNP) array‐based AM to guide targeted Sanger sequencing of EB candidate genes. Initially, 39 of the 46 cases were diagnosed with homozygous mutations using this method. Independently, 26 cases, including the seven initially unresolved cases, were analysed with an EB‐targeted next‐generation sequencing (NGS) panel. NGS identified mutations in five additional cases, initially undiagnosed due to the presence of compound heterozygosity, deep intronic mutations or runs of homozygosity below the set threshold of 2 Mb, for a total yield of 44 of 46 cases (95.7%) diagnosed genetically.